Perspektif Hukum Islam, Hukum Positif dan Mahasiswa Progam Studi PAI UIN Malang tentang Ganti Kelamin - Hani'ah, Wardatul; Hamidah, Tutik (Lembaga Yasin AlSys, 2024)
This study examines perspectives on gender transition from three viewpoints: students of the Islamic Education Program (PAI) at UIN Maulana Malik Ibrahim Malang, Indonesian positive law, and Islamic law. Using a qualitative narrative approach, interviews with ten PAI students revealed that the majority adhere to Islamic teachings, considering gender identity as a divine destiny that should not be altered, except in certain medical conditions. In Indonesian positive law, the process of gender transition is recognized through the court system with medical evidence. Meanwhile, in Islamic law, gender transition is generally rejected, except in cases of intersex. The Fatwa of the Indonesian Ulema Council (MUI) states that gender transition for individuals with a clear gender is haram but permissible in certain medical cases. This study concludes that the issue of gender transition is a complex debate involving religious, social, and legal aspects.